2016
DOI: 10.1038/srep17480
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes for accessing differential expression among developmental stages and analysis of differential expression of OBP genes in Anastrepha obliqua

Abstract: The West Indian fruit fly, Anastrepha obliqua, is an important agricultural pest in the New World. The use of pesticide-free methods to control invasive species such as this reinforces the search for genes potentially useful in their genetic control. Therefore, the study of chemosensory proteins involved with a range of responses to the chemical environment will help not only on the understanding of the species biology but may also help the development of environmentally friendly pest control strategies. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 62 publications
2
40
0
3
Order By: Relevance
“…This reflects the stable expression of EF‐1 α in lepidopteran insects under many experimental conditions, and this gene should be considered as a candidate RG in the gene expression analysis of lepidopteran insects in the future. In addition to lepidopterans, EF‐1 α has also performed well as an RG in other insects, such as Anastrepha oblique under different developmental stages (Nakamura et al., 2016), Bemisia tabaci across various abiotic conditions (Li et al., 2013), Drosophila melanogaster under heat‐stressed conditions (Ponton et al., 2011), Dicentrarchus labrax under nutritional/environmental changes (Schaeck et al., 2016), and Bactericera cockerelli under different life stages (Ibanez & Tamborindeguy, 2016). Nevertheless, EF‐1 α has also exhibited unstable expression in some insects, such as rice planthopper ( Delphacodes kuscheli ) under viral infection conditions (Maroniche et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the stable expression of EF‐1 α in lepidopteran insects under many experimental conditions, and this gene should be considered as a candidate RG in the gene expression analysis of lepidopteran insects in the future. In addition to lepidopterans, EF‐1 α has also performed well as an RG in other insects, such as Anastrepha oblique under different developmental stages (Nakamura et al., 2016), Bemisia tabaci across various abiotic conditions (Li et al., 2013), Drosophila melanogaster under heat‐stressed conditions (Ponton et al., 2011), Dicentrarchus labrax under nutritional/environmental changes (Schaeck et al., 2016), and Bactericera cockerelli under different life stages (Ibanez & Tamborindeguy, 2016). Nevertheless, EF‐1 α has also exhibited unstable expression in some insects, such as rice planthopper ( Delphacodes kuscheli ) under viral infection conditions (Maroniche et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were primarily conducted to select RGs that are stably expressed throughout different developmental stages, biological tissues, treatments, and environmental stresses (e.g., microbial infection and chemical stimulus) (Lord et al., 2010; Nakamura et al., 2016; Schaeck et al., 2016). They intensively focused on changes in gene expression associated with insecticide resistance, immunity, growth, and differentiation in laboratory populations.…”
Section: Introductionmentioning
confidence: 99%
“…In chordate phylum, many studies on identification of optimal RGs for gene expression normalization mainly focused on vertebrates, such as mammals, birds, fish and amphibian13141516, but information in amphioxus was limited. Several traditional RGs ( 18   S , ACT , EF1A , GAPDH , TUB and UBC ) have been widely used in qRT-PCR analyses in amphioxus, insects, human and plant17181920, but expression level of these RGs were variable to some degree under different conditions221. Wang et al firstly evaluated the reliability of candidate RGs and found EF1A was a useful RG in different tissues of amphioxus, but number of candidate RGs and algorithms were few in the study (four candidate RGs and two statistical methods)9.…”
mentioning
confidence: 99%
“…Assim como observado para os lepidópteros, Helicoverpa armigera (Shakeel et al, 2005;Chandra et a., 2014), Thitarodes armoricanus (Liu t al., 2016), Spodoptera exigua (Teng et al, 2012) e Spodoptera litura (Lu et al, 2013) . Uma baixa estabilidade para o referido gene também foi observada em Diabrotica virgifera virgifera (Rodrigues et al, 2014), e em mosca-das-frutas, Anastrepha obliqua (Nakamura et al, 2016). Tal divergência nos resultados pode ser devido ao fato deste gene estar diretamente envolvido em processos metabólicos.…”
Section: Discussionunclassified
“…A análise de expressão gênica através do RT-qPCR tem sido muito utilizada em estudos entomológicos visando compreender o comportamento dos insetos em condições bióticas, abióticas e em diferentes estádios de desenvolvimento (Ibanez & Tamborindeguy, 2016;Koramutla et al, 2016;Nakamura et al, 2016;Shakeel et al, 2015). Essa técnica permite quantificar a expressão de genes de interesse através da comparação do nível de expressão do mesmo através de genes de referência conhecidos por serem expressos de forma estável.…”
Section: Introductionunclassified